Urethral self-insertion of foreign body; a peculiar doorway to a psychiatric diagnosis: a case report - N. Gharbia; M. Chakroun; A. Hermi; A. Gharbia; S. Hmouda; H. Ayed; A. Aissa; A. Saadi; M. R. Ben Slama (BMC Urology)
Abstract Introduction Self-insertion of foreign bodies into the genitourinary tract is a rare but critical emergency, often underreported due to patient embarrassment. Such presentations may mask underlying psychiatric disorders, including acute psychotic episodes. This case report highlights a unique instance of urethral self-insertion of a plastic and metallic cable, which ultimately led to the diagnosis of schizophrenia. Case presentation A 32-year-old man with no prior medical or psychiatric history presented with acute penile pain of three hours’ duration. On examination, the patient remained calm, and a plastic cable was visibly protruding from the urethral meatus. A plain pelvic X-ray revealed a 9-cm radio-opaque foreign body along the urethral tract. After administering tetanus prophylaxis, the foreign bodies were successfully extracted under local anesthesia. Postoperatively, the patient experienced only mild urethrorrhagia and resumed normal urination. Given the unusual nature of the self-injurious behavior, a psychiatric evaluation was performed, which revealed an acute psychotic episode leading to a diagnosis of schizophrenia. Conclusion This case underscores the necessity for prompt urological intervention to prevent complications such as infection and urethral strictures, as well as the importance of thorough psychiatric evaluation in patients presenting with self-insertion injuries. A multidisciplinary approach integrating both acute physical management and long-term psychiatric care is essential to optimize outcomes and prevent recurrence.